EXPERIMENTAL INVESTIGATION ON THE PROPERTIES OF CEMENT CONCRETE PARTIALY REPLACED BY SILCA FUME AND FLY ASH - Khoso, Salim (Journal of Applied Engineering Science, 2016)
The aim of this research work is to investigate the optimum replacement of cement by silica fume and fly ash and to calculate the compressive strength of concrete. The cement has been replaced by fly ash and Silica fume varying in different percentage like 0%, 10%, 20%, 30%, 40% and 50% by weight of cement. Concrete specimens of ratios 1:2:4 and 1:1.5:3 were prepared, cured, tested and compared in term of compressive and split tensile strength with the traditional concrete. Tests were conducted to calculate the mechanical properties for the concrete ranging from 7, 14 and 28 days curing both for compressive and split tensile strength. It has been observed that the compressive strength increases when cement is replaced 10% by Silica fume and Fly ash. However, the compressive strength is gradually reduced when the cement replaced more than 10%. The effect of Silica fume and Fly ash on various other concrete properties has also been investigated in this paper. It has also been observed that the use of Silica fume and Fly ash not only improve the various properties of concrete but could also be economical in cost of construction.